2022
DOI: 10.3390/nano12203563
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Imbibition Oil Recovery by Natural Surfactant/Nanofluid: An Experimental and Theoretical Study

Abstract: Organic surfactants have been utilized with different nanoparticles in enhanced oil recovery (EOR) operations due to the synergic mechanisms of nanofluid stabilization, wettability alteration, and oil-water interfacial tension reduction. However, investment and environmental issues are the main concerns to make the operation more practical. The present study introduces a natural and cost-effective surfactant named Azarboo for modifying the surface traits of silica nanoparticles for more efficient EOR. Surface-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Part of the crude oil at in-depth is exchanged to near the fracture. The imbibition oil recovery is closely related to reservoir permeability, interfacial tension, wettability, and oil viscosity. , After soaking for a period of time, the well is opened and produced. The formed high-pressure energy establishes a displacement relationship with the oil in the pores, forming the driving force for the reverse unsteady displacement of oil.…”
Section: Resultsmentioning
confidence: 99%
“…Part of the crude oil at in-depth is exchanged to near the fracture. The imbibition oil recovery is closely related to reservoir permeability, interfacial tension, wettability, and oil viscosity. , After soaking for a period of time, the well is opened and produced. The formed high-pressure energy establishes a displacement relationship with the oil in the pores, forming the driving force for the reverse unsteady displacement of oil.…”
Section: Resultsmentioning
confidence: 99%
“…Khoramian et al developed surface-modified nanoparticles by synthesizing surfactant Azarboo with silica nanoparticles and demonstrated that these modified nanoparticles could enhance oil recovery, as evidenced by changes in sample wettability. 31 Liu et al investigated the optimal formulation of nanoparticle− surfactant compound solutions for varying enhanced oil recovery (EOR) objectives. 32 Additionally, Hou et al, utilizing the HWBE process, examined the synergistic effects of nanoparticle−surfactant compound solution on improving the recovery efficiency of carbonate bituminous rocks.…”
Section: Introductionmentioning
confidence: 99%
“…Khoramian et al. developed surface-modified nanoparticles by synthesizing surfactant Azarboo with silica nanoparticles and demonstrated that these modified nanoparticles could enhance oil recovery, as evidenced by changes in sample wettability . Liu et al investigated the optimal formulation of nanoparticle–surfactant compound solutions for varying enhanced oil recovery (EOR) objectives .…”
Section: Introductionmentioning
confidence: 99%
“…An alternative strategy involves removing the fouled oil from surfaces through cleaning following the occurrence of oil fouling. However, this approach usually requires various surfactants and detergents, which generate emulsion wastewater and cause metal surface corrosion. Thus, the self-cleaning of fouled surfaces, by in situ photodegradation, has been investigated.…”
Section: Introductionmentioning
confidence: 99%